The dynamics of Australian stock indices and commodities based on MGARCH-DCC and wavelet techniques - Ahmad Monir Abdullah; Hishamuddin Abdul Wahab; Mohd Fahmi Ghazali; Mohd Hasimi Yaacob; Abul Mansur Mohammed Masih (Cogent Business & Management, 2022)
This paper aims to investigate the extent of hedging and diversification opportunities available for an Australian investor who holds a portfolio consisting of Australian conventional and Islamic indices, crude oil, gold, Bitcoin, and the Australia-US exchange rate of daily data from 2011 to 2021. The relevant time-varying and time-scale dependent techniques, such as MGARCH dynamic conditional correlation (MGARCH-DCC), continuous wavelet transform (CWT), and maximal overlap discrete wavelet transform (MODWT) are employed to discern the correlation and volatilities of the variables. The paper's unique contribution lies in unveiling an Australian investor's diversification opportunities of a portfolio containing Bitcoin, gold, oil, Islamic indices, conventional indices, and exchange rates. Findings from MGARCH-DCC analysis suggest that Bitcoin is the least correlated variable. However, investors may be discouraged from choosing Bitcoin as a diversification instrument due to its high volatility. The evidence further suggests that Australian investors may benefit from diversification with gold. Nonetheless, the CWT result shows that the diversification benefits effects will last for a holding period no longer than 64 days. Our research findings tend to indicate the importance of finding diversification opportunities for investors with heterogeneous investment holdings over various periods by utilising relatively advanced techniques.
Keywords: G15; E44; C22; C58; 650; bitcoin; gold; conventional stock index returns (CSIR); crude oil; CWT; Islamic stock index returns (ISIR); MGARCH-DCC; MODWT; Portfolio diversification benefits